FACTORS ANALYSIS OF THE INFLUENCE OF DELAY IN DELIVERY OF EXPORT PRODUCTS AT PT BATIK DANAR HADI SURAKARTA - Jeremy Ritoni Alfajri; Sri Hartono; Sarsono Sarsono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
One form of delivery of goods or delivery for companies apart from distributing their own production can also receive orders from other companies, as consumers of delivery of their export goods. Of course, all consumers will definitely choose the best service in handling their goods (shipment) until the delivery process or reaching the consignee. The formulation of the problem in the research, namely what factors affect the delay in the delivery of export products at PT. Batik Danar Hadi Surakarta? The research objectives are: 1) To determine the effect of product distribution channels on delays in the delivery of export products at PT. Batik Danar Hadi Surakarta, and 2) Describe the distribution channel of export product delivery at PT. Batik Danar Hadi Surakarta. This type of descriptive exploratory research with quantitative analytical approach is used to determine the causal relationship between two or more variables in an observational way. The population is the export customers of the company PT. Batik Danar Hadi Surakarta with a sample of 100 customers by simple random sampling. The data analysis technique used multiple linear regression, F test, t test, and coefficient of determination. The results of the study show 1) There is an influence of distribution channels on the delay in the delivery of export products of PT. Danar Hadi Batik in Surakarta. 2) There is an influence of the transportation system on the delay in the delivery of export products of PT. Danar Hadi Batik in Surakarta. Keywords: Delivery, Distribution Channel, Transportation System.